NEGOTIATION OF HADITH WITH THE TRADITION OF BOWING AT PESANTREN RAUDHATUT THALIBIN REMBANG - Ahmad Syahid (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Religion and culture are sources of values and norms in society. However, the narrow interpretation of religious narrative puts it in a position that is contrary to the culture, such as the culture of bowing practiced by students at Pesantren Raudhatut Thalibin. In this connection, intense dialogue with various values is needed to bring forth an explanation that religion and culture in the context of Indonesian Islam are inseparable. This study aims to explain the validity of the culture of bowing in religious narratives. To achieve this purpose, this study is a qualitative study with an interactive model of analysis, which includes three stages, namely data reduction, data display, and conclusion drawing. The results of this study explain that bowing is the local wisdom of the Javanese people that does not conflict with religious texts. The culture of bowing is a form of respect for older people. It is an internalization of religious texts with a sociocultural dimension because of the existing interpretation patterns and social construction in the form of religious attitudes and behavior in practicing Islamic teachings.